Flood risk management learning to live with rivers - Fleming, George (Thomas Telford, 2002)
Outlining the policy and practice of managing flood risk, this book also includes a review of the application of statistical and computational modelling approaches to flood estimation, and guidance on the use of the 'Flood Estimation Handbook'. It is useful for water engineers, local authorities, and water companies.